CASK related disorder: Epilepsy and developmental outcome. (March 2021) - Giacomini, Thea; Nuovo, Sara; Zanni, Ginevra; Mancardi, Maria Margherita; Cusmai, Raffaella; Pepi, Chiara; Bertini, Enrico; Valente, Enza Maria; Battini, Roberta; Ferrari, Annarita; Romaniello, Romina; Zucca, Claudio; et al.
Abstract: Objective: CASK pathogenic variants are associated with variable features, as intellectual disability, optic atrophy, brainstem/cerebellar hypoplasia, and epileptic encephalopathy. Few studies describe the electroclinical features of epilepsy in patients with CASK pathogenic variants and their relationship with developmental delay. Methods: this national multicentre cohort included genetically confirmed patients with different CASK pathogenic variants. Our findings were compared with cohorts reported in the literature. Results: we collected 34 patients (29 females) showing from moderate (4 patients) to severe (22) and profound (8) developmental delay; all showed pontine and cerebellar hypoplasia, all except three with microcephaly. Seventeen out of 34 patients (50%) suffered from epileptic seizures, including spasms (11 patients, 32.3%), generalized (5) or focal seizures (1). In 8/17 individuals (47.1%), epilepsy started at or beyond the age of 24 months. Seven (3 males) out of the 11 children with spasms showed EEG features and a course supporting the diagnosis of a developmental and epileptic encephalopathy (DEE). Drug resistance was frequent in our cohort (52.9% of patients with epilepsy). EEG abnormalities included poorly organized background activity with diffuse or multifocal epileptiform abnormalities and sleep-activation, with possible appearance over the follow-up period. Developmental delay degree was not statistically different among patients with or without seizures but feeding difficulties were more frequent in patients with epilepsy. Conclusions: epilepsy is a frequent comorbidity with a high incidence of spasms and drug resistance. Overall developmental disability does not seem to be more severe in the group of patients with epilepsy nor to be linked to specific epilepsy/EEG characteristics. A childhood onset of epilepsy is frequent, with possible worsening over time, so that serial and systematic monitoring is mandatory. Highlights: CASK pathogenic variants are associated with a high incidence of epilepsy. Epilepsy features are late onset of seizures, presence of spasms, drug-resistance. Developmental delay does not seem to be more severe in the patients with epilepsy.